MK8722, an AMPK activator, inhibiting carcinoma proliferation, invasion and migration in human pancreatic cancer cells - Cheng Wang (Elsevier, 2021)
Background: MK8722 is a potent and systemic pan-AMPK activator. It is an effective, direct, allosteric activator of AMPK complex in many mammals. This study tried to explore the underlying anti-cancer molecular mechanism of MK8722 in human pancreatic cancer cells (PCCs). Methods: The anti-proliferation, invasion and migration functions of MK8722 in human pancreatic cancer analyzed by real time cellular analysis, colony formation assay, cell migration assay, transwell assay and flow cytometery analysis. Moreover, the potential targeted signaling pathway was tested via RNA-seq and pathway enrichment analysis. Results: In the present study, we investigated the anti-PCCs effects of MK8722 on two different human pancreatic cancer cell lines (PANC-1 and Patu8988). The results showed that MK8722 significantly inhibited human tumor cells proliferation and migration/invasion in a dose-dependent manner. Additionally, the influence of MK8722 was examined by analyzing the expression of potential key genes and pathways, which may provide novel insights to the mechanism of MK8722. Conclusion: The inhibition of pancreatic cancer by MK8722 through a number of pathways that inhibit carcinoma proliferation, invasion and migration. The potential effect of MK8722 might be determined by regulating the expression of AL162151, IER2, REPIN1, KRT80 to inhibit cycle arrest and migration.